2011
DOI: 10.1111/j.2042-7158.2011.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

The application and limitations of mathematical modelling in the prediction of permeability across mammalian skin and polydimethylsiloxane membranes

Abstract: While the results of this study indicate that permeation across rodent (mouse and rat) and pig skin is, in a statistical sense, similar, and that the artificial membranes are poor replacements of human or animal skin, the overriding issue raised in this study is the nature of the dataset and how it can influence the results, and subsequent interpretation, of any model produced for particular membranes. The size of the datasets, in both absolute and comparative senses, appears to influence model quality. Ideall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 99 publications
0
28
0
Order By: Relevance
“…Also, the studies on absorption of toxic compounds through the skin are scarce with animal skin such as rodent and pig as a weak substitute [122]. Similar studies by AgatonovicKustrin et al and Cheng et al have published on use of ANNs in determining the quantitative structure-permeability relationship of penetration across skin or polydimethylsiloxane membranes as the model of skin permeation [123][124][125][126].…”
Section: Prediction Permeability Of Skin and Blood Brain Barriermentioning
confidence: 99%
“…Also, the studies on absorption of toxic compounds through the skin are scarce with animal skin such as rodent and pig as a weak substitute [122]. Similar studies by AgatonovicKustrin et al and Cheng et al have published on use of ANNs in determining the quantitative structure-permeability relationship of penetration across skin or polydimethylsiloxane membranes as the model of skin permeation [123][124][125][126].…”
Section: Prediction Permeability Of Skin and Blood Brain Barriermentioning
confidence: 99%
“…Various kinds of empirical and mathematical models for the correlation and prediction of human skin permeability, as log Kp, have been reported (Baba et al, 2015;Mitragotri, 2003), and there have been a number of reviews of these models (Chen et al, 2013;Geinoz et al, 2004;Mitragotri et al, 2011;Moss et al, 2011;Neely et al, 2009). It has been known for years that the permeability of ionizable compounds depends on the pH of the donor solution, attributed to the slower rate of permeation of ionic species compared to the corresponding neutral species (Roy and Flynn, 1990;Swarbrick et al, 1984;Waters and Bhuiyan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2009) observed that J max showed a more or less parabolic relationship with log K OW for similar sized permeants, Magee (1998) (cited in Moss et al, 2002) demonstrated that hydrogen bonding is more important in the most hydrophobic group of chemicals and Moss et al (2011) showed that the relation between measured k p -values and important properties determining permeation is non-linear.…”
Section: Qsarsmentioning
confidence: 99%
“…These novel models are able to predict non-linear processes, and Gaussian process models have been shown to perform better than selected QSPRs (see Moss et al, 2011) as have fuzzy models and artificial neural networks (Russell and Guy, 2009). However, they yet have to prove their practical value (Mitragotri et al, 2011).…”
Section: Qsarsmentioning
confidence: 99%
See 1 more Smart Citation